PTH-062 Interventional management of central venous thromboses associated with central venous catheters: our attempts are not in vein. (23rd September 2015) - Murugananthan, A U; Paskaran, P; Khoo, M M Y; Naji, Y; Tran, T; Nightingale, J M D; Gabe, S M
Abstract : Introduction: Central venous thrombosis (CVT) associated with a central venous catheter (CVC) has an incidence of 0.027 episodes per catheter per year in parenteral nutrition use.1 Loss of venous access may occur, with loss of two or more central veins being an indication for intestinal transplantation. We describe a 4-year single centre experience of the interventional management of CVT associated with CVCs. Methods: Patients who underwent interventional management of their CVTs were identified and clinical records assessed. Upper limb catheter position was recorded as described previously.2 Results: Nine (eight females) patients underwent 10 interventions. Mean age: 48.8 years (range 22–67). Intestinal failure aetiology: functional (3), Crohn's disease (3), mesenteric infarction (2) and FAP/desmoid disease.1 Six patients were smokers and two were on anti-coagulant therapy. Seven patients were on intravenous nutrition and 2 on parenteral fluids only. Mean duration of parenteral therapy was 4.4 years and the catheters were in situ for 19.2 months (mean, range 1 month–8 years). Interventions are summarised in Abstract 062 . Four out of nine patients were noted to have a proximal catheter tip position at the time of thrombosis. Two patients developed complications of bleeding after thrombolysis (one at venepuncture site and the other developed occult GI bleeding) but required no therapy. 30-day mortality was 1 patient, unrelated to thrombosis. Conclusion: We show that local thrombolysis, venoplasty and venous stenting are safe and when used in combination re-establish venous patency in 70%.